Atezolizumab-Induced Autoimmune Diabetes in a Patient With Metastatic Lung Cancer - Sothornwit, Jin; Phunmanee, Anakapong; Pongchaiyakul, Chatlert (Frontiers in Endocrinology, 2019)
Context. Immune checkpoint inhibitors (ICIs), now FDA-approved, are increasingly used as an effective treatment of various cancers. Autoimmune diabetes is a rare but life-threatening endocrine adverse event, which has been reported in patients treated with anti-programmed-cell death-1 (anti-PD-1) and anti-programmed-cell death-1 ligand (anti-PD-L1) therapies. Case description. We report a 52-year-old woman with advanced-stage non-small cell lung cancer who presented with diabetic ketoacidosis (DKA) at 24 weeks after atezolizumab initiation. She initially received oral antidiabetic medication from primary care hospital,and experienced recurrent DKA three days later. Her plasma glucose on the day that she had recurrent DKA was 332 mg/dL (18.4 mmol/L), A1c was 7.9% (63 mmol/mol), fasting C-peptide was less than 0.03 nmol/L (0.1 ng/ml), fasting insulin level was less than 1 μIU/ml, anti-glutamic acid decarboxylase 65 (GADA) was 7.2 U/ml (normal, >5 U/ml), and human leukocyte antigen (HLA) class II typing was DR3-DQ2/DR14-DQ5. A diagnosis of autoimmune diabetes was made. After treatment for DKA, she recovered and received basal-bolus insulin treatment. Atezolizumab had been discontinued after the fifth cycle, prior to the development of DKA, due to progression of lung cancer. Conclusion. To date, there has been neither an effective way to detect if a patient is at high risk for autoimmune diabetes nor to prevent the complications associated with it. Regular glucose monitoring is the best method of early diabetes detection. In patients with new onset diabetes following treatment with ICIs, C-peptide levels and GADA should be screened, and insulin therapy should be prescribed to prevent hyperglycemic emergency while waiting for definite diagnosis.